Captivity beyond prisons: criminalization experiences of Latina (im)migrants - Escobar, Martha D. (University of Texas Press, 2016)
Introduction : shifting the conversation from (im)migrant rights to abolition -- Understanding the roots of Latina (im)migrants' captivity -- Reinforcing gendered racial boundaries : unintended consequences of (im)migrant rights discourse -- Violent formations : criminalizing and disciplining (im)migrant women -- Domesticating (im)migration : coordinating state violence beyond the nation-state -- Emancipation is not freedom : a reflection and critique of advocacy abolition -- Conclusion : envisioning and performing freedom